Diabetes and COVID-19; A Bidirectional Interplay - Kazakou, Paraskevi; Lambadiari, Vaia; Ikonomidis, Ignatios; Kountouri, Aikaterini; Panagopoulos, Georgios; Athanasopoulos, Stavros; Korompoki, Eleni; Kalomenidis, Ioannis; Dimopoulos, Meletios A.; Mitrakou, Asimina (Frontiers in Endocrinology, 2022)
There seems to be a bidirectional interplay between Diabetes mellitus (DM) and coronavirus disease 2019 (COVID-19). On the one hand, people with diabetes are at higher risk of fatal or critical care unit-treated COVID-19 as well as COVID-19 related health complications compared to individuals without diabetes. On the other hand, clinical data so far suggest that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may result in metabolic dysregulation and in impaired glucose homeostasis. In addition, emerging data on new onset DM in previously infected with SARS-CoV-2 patients, reinforce the hypothesis of a direct effect of SARS-CoV-2 on glucose metabolism. Attempting to find the culprit, we currently know that the pancreas and the endothelium have been found to express Angiotensin-converting enzyme 2 (ACE2) receptors, the main binding site of the virus. To move from bench to bedside, understanding the effects of COVID-19 on metabolism and glucose homeostasis is crucial to prevent and manage complications related to COVID-19 and support recovering patients. In this article we review the potential underlying pathophysiological mechanisms between COVID-19 and glucose dysregulation as well as the effects of antidiabetic treatment in patients with diabetes and COVID-19.